Emerging trends and challenges in international student research: A content analysis of recent dissertations (2022–2024) - Bista, Krishna; Oladipo, Oluwasegun Adesola; Ge, Lin; Qin, Tian (Journal of International Students, 2026)
This study presents a content analysis of 470 doctoral dissertations published between 2022 and 2024, examining emerging trends, theoretical frameworks, and research approaches related to international students. Using a qualitative content analysis approach and descriptive statistics, the study systematically analyzed the dissertations to identify recurring themes and issues. The key themes identified include teaching and learning; academic practices; acculturation and intercultural competence; career development and leadership; experiences and challenges; mobility and policy contexts; social diversity and inclusion; institutional support; and well-being. The findings show a predominant use of qualitative methods, a concentration on U.S.-based contexts, and a strong disciplinary focus on higher education. Gaps include insufficient attention to digital and online education, underrepresentation of non-Western regions, and insufficient theoretical grounding. The study underscores the need for more inclusive, interdisciplinary, and methodologically diverse research to inform policies and practices that support international students’ academic success, well-being, and global mobility.